Ozone fluidized bed catalyst and preparation method thereof
By using the ozone fluidized bed catalyst prepared by the fluoropolymer aqueous emulsion and wet coating method, the problem of difficult catalyst to fully fluidize under limited power conditions is solved, and low addition, high fluidization efficiency and low Effects of running costs.
Patent Information
- Application Number
- CN202411526155.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing ozone fluidized bed catalysts are difficult to fully fluidize under limited power conditions, resulting in a decrease in reaction rate and an increase in fluidized power costs, limiting the large-scale application of this technology.
Using fluoropolymer aqueous emulsion as the matrix, the carbon-based material powder and the catalyst powder are dispersed into a catalyst suspension by mechanical stirring or phacoemulsification, and then a catalyst film is prepared by wet coating method, and an ozone stream is prepared by sintering and other steps. Fluid bed catalyst.
The low dosage and high fluidization efficiency of the catalyst are achieved, the fluidization dynamic conditions are reduced, the process operation costs are reduced, and the wear resistance and service life of the catalyst are improved.
Smart Images

Figure BDA0005109270790000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of sewage treatment, and in particular to an ozone fluidized bed catalyst and a preparation method thereof. Background Art
[0002] Ozone catalytic oxidation advanced oxidation technology uses a catalyst to catalytically decompose ozone into hydroxyl free radicals with stronger oxidizing properties, and further oxidizes and decomposes toxic and difficult-to-degrade organic pollutants. Due to its high oxidizing ability, this technology can more thoroughly mineralize and decompose organic pollutants, and its final products are non-toxic and harmless carbon dioxide and water, thereby effectively reducing the biological toxicity of raw water. At the same time, the oxidizing ability of hydroxyl free radicals is not selective, so it has a wider range of applications. It is often used in wastewater fields such as landfill leachate, textiles, chemical synthesis and chemical industries, especially in scenarios where traditional processes such as biochemical, flocculation and physical separation cannot be used.
[0003] The ozone catalytic oxidation process often adopts the fixed bed contact oxidation method. The mass transfer process between the various reactants involved in the catalytic oxidation process can be simply described as: ozone is added to the active sites of the catalyst in a fixed manner in a static state, and catalytically decomposed into hydroxyl radicals on the catalyst surface. The organic pollutants in the raw water diffuse to the catalyst surface with the influent water flow and combine with the active sites, and then are oxidized by ozone and free radicals. In this way, the reaction rate is highly controllable, and the relationship between the reaction time and the COD removal rate is easy to quantify, which is convenient for process design. However, the fixed bed ozone catalytic oxidation technology also has shortcomings: 1. The reaction rate is limited by the specific surface area and the number of active sites of the catalyst, making it difficult to improve the mass transfer efficiency; 2. The amount of catalyst is large, which pushes up the construction investment cost; 3. The catalyst is in a static state in the reactor and is easily blocked by suspended particles; 4. The catalyst is easily contaminated, easy to scale and agglomerate, and an additional backwashing system is required. Therefore, the ozone water treatment industry is in urgent need of an alternative technology with a small amount of catalyst, high mass transfer efficiency, and operating cost advantages. Among them, the ozone fluidized bed catalytic oxidation technology (abbreviated as ozone fluidized bed) has the most potential.
[0004] Ozone fluidized bed water treatment technology is a gas-liquid-solid three-phase fluidized bed reaction, generally composed of an ozone source (air or a mixed flow of oxygen and ozone), a reactor, a fluidizing device and a fluidized bed catalyst. The fluidization power provided by the ozone gas flow and the rising flow rate provided by the internal circulation of the liquid phase are used to fully contact the fluidized bed catalyst, ozone and liquid sewage. This depends on the full fluidization of the catalyst in the reactor. Even if the dosage is less than that of the fixed bed, good mass transfer efficiency and reaction rate can be achieved. However, due to the inherent process conditions such as the outlet pressure of the ozone generator, the amount of ozone added, the effective liquid level and the specifications of the reflux pump, it is difficult to directly fluidize the fluidized bed catalyst in the traditional chemical synthesis field, resulting in a decrease in reaction rate and an increase in the cost of fluidization power, which limits the large-scale application of this technology and is a technical difficulty that is a consensus in the industry. Therefore, it is urgent to design an ozone catalyst that can be fully fluidized under limited power conditions.
[0005] Previous patent technologies focused on optimizing ozone fluidized bed reactions from the perspectives of reactor type (such as internal circulation central tube reactor, patents CN110818064A, CN114684972A), fluidizing device (such as internal circulation jet aeration, patent CN114956296), fluidized bed coupling with other processes (such as fluidized bed coupling with membrane filtration, patent CN104529001B), and additional catalyst mixing settings (such as umbrella-type agitators, patent CN213506156U), but there was little research on catalysts.
[0006] However, fluidized bed catalysts used in the field of chemical synthesis are difficult to be directly used in ozone fluidized beds due to differences in process conditions. Patent CN110548520 uses an impregnation method to prepare an activated alumina-based catalyst with a size of 20-120 mesh, but does not disclose the use effect in the ozone fluidized bed process, nor does it mention the required fluidization process conditions. Patent CN115591554A uses a spray drying method to prepare an ozone fluidized bed catalyst with a size of 10-500 microns, but does not disclose the use effect and required process conditions. Summary of the invention
[0007] In order to solve the above technical problems, the purpose of the present invention is to provide an ozone fluidized bed catalyst which is easy to fully fluidize and has an advantage in reaction rate and a preparation method thereof.
[0008] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is a method for preparing an ozone fluidized bed catalyst, characterized in that it comprises the following steps:
[0009] Step 1, preparing a fluorine-containing polymer aqueous emulsion;
[0010] Step 2: adding a certain mass of carbon-based material powder and catalyst powder into the fluorine-containing polymer aqueous emulsion and dispersing them into a catalyst suspension;
[0011] Step 3, applying the catalyst suspension to the substrate by a wet coating method, and preparing a catalyst film by solvent drying, sintering, cooling, peeling and washing;
[0012] Step 4: Cut the catalyst film into a certain size to finally obtain a fluidized bed catalyst.
[0013] In the above technical solution, the dispersion process in step 2 is mechanical stirring or ultrasonic emulsification. The dispersed mixed solution is ready for use and the storage time does not exceed 2 hours.
[0014] According to a preferred technical solution, the aqueous fluorine-containing polymer emulsion in step 1 is composed of fluorine-containing emulsion A and fluorine-containing dispersion B, and the effective solid mass ratio of fluorine-containing emulsion A to fluorine-containing dispersion B is 40-80:1.
[0015] In a further technical solution, the fluorine-containing emulsion A is a polytetrafluoroethylene resin aqueous emulsion, and the fluorine-containing dispersion B is a perfluorosulfonic acid resin dispersion; the solid content of the fluorine emulsion A is 45-70%, and the average diameter of the polytetrafluoroethylene resin is 0.2-0.5 μm; the solid content of the fluorine-containing dispersion B is 10-25%, and the average diameter of the fluorinated resin is 0.05-0.1 μm.
[0016] In the above technical solution, the polytetrafluoroethylene resin aqueous emulsion is made of hydrophobic polytetrafluoroethylene resin (PTFE) polymer, prepared by an emulsion polymerization process known in the industry, and generally contains a small amount of (fluorinated) surfactant and stabilizer.
[0017] In a further technical solution, the fluorinated dispersion B is composed of an unsaturated perfluoroolefin monomer and a -SO 2 Perfluorosulfonic acid resin dispersion prepared from perfluorovinyl ether monomer with F functional group.
[0018] In the above technical solution, the sulfonyl group (-SO 2 F) functional group fluorinated resin copolymer (PFSR), is composed of unsaturated perfluoroolefin monomer and containing at least one -SO 2 The aqueous dispersion of the F-functional perfluorovinyl ether monomer prepared by conventional emulsion process. Generally, at the end of the reaction, the fluorosulfonyl group will be converted into a sulfonic acid group to form a perfluorosulfonic acid resin dispersion, which usually contains a small amount of fluorinated ionic surfactant (such as fluorinated carboxylic acid or sulfonate).
[0019] In a further technical solution, the unsaturated perfluoroolefin monomer is one of the C2-C6 perfluoroolefins; the chemical formula of the perfluorovinyl ether monomer is F 2 C=CF-O-[CF 2 ]n-SO 2 F, wherein n = 1-4.
[0020] According to a preferred technical solution, the carbon-based material powder in step 2 is powdered activated carbon or carbon nanotubes or graphene, the carbon-based material powder accounts for 0.5%-4% of the solid content of the fluorine-containing polymer aqueous emulsion, and the particle size of the carbon-based material powder is 800 mesh.
[0021] A preferred technical solution is that the catalyst powder in step 2 is 1-3 of the oxide powders of Fe, Mn, Cu, Ni, Ce, Mg, Sn, Bi, Ag and Au, the catalyst powder accounts for 5%-30% of the solid content of the fluoropolymer aqueous emulsion, and the particle size of the catalyst powder is greater than or equal to 300 mesh.
[0022] In the above technical solution, the preferred range of the solid content of the catalyst powder in the fluorine-containing polymer aqueous emulsion is 10-20%. The particle size of the catalyst powder is preferably 100 nm.
[0023] The preferred technical solution is that the wet coating method in step three uses high boron glass or stainless steel plate material as the substrate. The TM2300pro vacuum scraper coater can be used in the laboratory, and its main operating parameters are: coating speed range 5-250mm / s, preferably 50-100mm / s; coating thickness range 0.1-10mm, preferably not less than 0.2mm and not more than 3mm; bottom plate heating range RT-180℃, generally set to 75-120℃, for preliminary drying of the solvent.
[0024] The preferred technical solution is that in step three, the dried catalyst film is transferred to a muffle furnace for sintering. The sintering temperature is generally 200-280°C, the heating rate is 10°C / min, the maximum temperature sintering time does not exceed 30min, and the cooling condition is to stop heating until the temperature drops below 150°C, and cool naturally after taking it out. The cooled catalyst film is generally peeled off from the substrate, otherwise it can be peeled off from the corners with the help of a release scraper, and cut into square sheets of about 3-5mm, that is, the finished ozone fluidized bed catalyst is obtained. The "cracks" on the general catalyst film have no obvious effect on the performance of the catalyst, unless the cracks cause the catalyst film to break to less than 3mm, which may cause the catalyst to be lost during the ozone catalytic reaction. If the above-mentioned breakage phenomenon occurs, generally reducing the heating rate and sintering time can improve the "cracks" phenomenon. The rinsing condition is to rinse with pure water until the rinse liquid no longer foams and is neutral. Remove the excess surfactant and obtain a dry catalyst product after drying.
[0025] According to a preferred technical solution, in step 4, the catalyst film is cut into square sheets with a side length of 3-5 mm.
[0026] Catalyst fluidization performance test.
[0027] The fluidization performance test of the catalyst can be carried out in the laboratory using a conventional ozone fluidized bed reactor. The main process parameters of the equipment are: the ozone equivalent of the oxygen source ozone generator is 15g / h, the maximum flow rate of the oxygen generator gas source is 5L / min, the flow rate range of the reflux pump is 0-5L / min, and the rated head is 2 meters. The difficulty of evaluating the fluidization of the catalyst bed is expressed by the fluidization conditions when the catalyst bed occupying 30% of the volume of the reaction zone expands by 50%. The fluidization conditions are the aeration intensity provided by the ozone mixer (unit L / (m 2 хs)), the gas flow rate through the cross-sectional area of the fluidized zone per second; and the backwash intensity of the catalyst bed by liquid reflux (unit L (m 2 хs)) is the liquid flow rate passing through the catalyst bed interface per second. The smaller the "aeration intensity" and "backwash intensity" when the bed expands by 50%, the easier the catalyst is to fluidize and the smaller the fluidization power required.
[0028] Simulated pollutant removal performance test of ozone fluidized bed reaction.
[0029] Sodium citrate was used to simulate the target pollutant, and an aqueous solution with a COD of about 800 mg / L was prepared as the simulated wastewater for the ozone fluidized bed performance test. The effective water volume of the reactor was about 3.5 L, and the ozone dosage (O 3 :COD) is fixed at 2:1, and O 3 The theoretical demand equivalent is 5.6g / L, at which time the ozone concentration is about 60-65mg / L, and the calculated flow rate of the ozone mixture is about 1.5L / min. Determine the amount of catalyst: Add a certain amount of fluidized bed catalyst into the reaction filled with wastewater, and adjust the height of the fluidized bed layer in the reaction zone to about 60% of the total height of the reaction zone by adjusting the flow rate of the reflux pump, but the maximum flow rate does not exceed 14L / h, that is, the reflux ratio does not exceed 400%. If the above fluidization conditions cannot reach 60% expansion height, the catalyst needs to be added. Correspondingly, the loading amount of the fixed bed catalyst used for comparison is also 60% of the reaction zone. The reaction time of ozone catalytic oxidation is 60min, and the average value of three reactions is taken to record the COD removal rate.
[0030] Evaluation of the attrition resistance of the catalyst.
[0031] The method for evaluating fluidized bed catalysts in the petrochemical industry in the NB / SH / T0943-2017 national standard (air jet method) was used to evaluate the wear performance of the finished catalyst. This method can be simply described as taking a certain amount of catalyst soaked in water, fluidizing it under an air flow of 10L / min, collecting the fine powder of the catalyst grinding product, and calculating the percentage of catalyst weight loss within 1 hour (L 1h ), the smaller the value is, the better the wear resistance of the catalyst is.
[0032] The advantages of the present invention are:
[0033] 1. The present invention greatly reduces the amount of catalyst added. Using the same active component, the amount of catalyst added is about 1 / 3 of that of a fixed bed catalyst made of φ3-5mm γ-alumina balls, and about 1 / 2 of that of a fluidized bed catalyst made of 30 mesh (<0.55mm) active alumina powder;
[0034] 2. The present invention has lower fluidization dynamic conditions, does not require jet aeration, and reduces process operation costs. To achieve a 50% catalyst bed height expansion rate, the required ozone aeration intensity is only 1.55L / (m 2 хs), no reflux is required to provide an upward flow rate, and the 30-mesh powder catalyst used for comparison requires 4.14 L / (m 2 хs) aeration intensity, 2.41L / (m 2 хs) backwash strength, and the fixed bed catalyst cannot expand by 50% under the experimental conditions of this patent;
[0035] 3. The ozone fluidized bed catalyst of the present invention can naturally settle to the bottom of the reactor after the fluidization is stopped, is not easy to lose and is easy to recover, has strong wear resistance and a long service life. DETAILED DESCRIPTION
[0036] Embodiment 1:
[0037] Fluorine-containing emulsion A is a polytetrafluoroethylene resin (PTFE) emulsion with a solid content of 60%, and fluorine-containing emulsion B is a tetrafluoroethylene-perfluoro (3-oxa-4-pentene sulfonic acid) copolymer aqueous dispersion with a solid content of 25%. The trade name is D72-25BS. 200 g of fluorinated emulsion A and 12 g of fluorinated emulsion B were mixed and mechanically stirred for 15 min to obtain a fluorinated polymer aqueous emulsion, and the solid mass ratio of the two resins was 40:1.
[0038] Add 24.6 g of Fe (mass ratio 2:1) to the above solution. 2 O 3 and MnO 2 The mixed powder has a particle diameter greater than 300 mesh, accounting for 20% of the solid mass of the fluoropolymer aqueous emulsion. Then 2.46g of 800 mesh coal-based activated carbon powder is added, accounting for 2% of the solid mass of the fluoropolymer aqueous emulsion. The mixed solution is transferred to an ice water bath and ultrasonically emulsified for 15 minutes to obtain a catalyst suspension.
[0039] The above suspension was used for coating, with high boron glass as the substrate, the coating speed was 50 mm / s, the coating thickness was 0.6 mm, the bottom plate temperature was 75°C, and the coating was dried for 5 minutes after coating. After drying, the substrate was transferred to a muffle furnace for sintering.
[0040] The above sintering conditions are as follows: heating rate of 10°C / min, heating to 250°C and keeping the temperature for 15 minutes, stopping heating and cooling naturally to below 150°C, and cooling to room temperature.
[0041] The stripped catalyst film is cut into thin slices of about 3-5 mm, and washed with pure water until the washing liquid no longer bubbles and is neutral, and then dried to obtain the ozone fluidized bed catalyst.
[0042] The fluidization condition when the catalyst volume of 30% of the reaction zone volume expands by 50% is the aeration intensity of 1.55 L / (m 2 хs), no reflux is required. The abrasion-resistant weight loss percentage of the catalyst L1h <3.9%. The pollutant removal capacity of the catalyst is evaluated by adding about 500mL of catalyst into the reactor, adjusting the ozone / oxygen mixed gas flow rate to 1.5L / min, and stabilizing the ozone concentration at 60-65mg / L. There is no need to start the reflux pump, and the bed can expand to 60% of the reactor height. The virtual wastewater with COD = 800mg / L is treated under the above conditions, and the COD removal rate after 1h of reaction is about 82% on three averages.
[0043] Embodiment 2:
[0044] Fluorine-containing emulsion A is a polytetrafluoroethylene resin (PTFE) emulsion with a solid content of 60%, and fluorine-containing emulsion B is a tetrafluoroethylene-perfluoro (3-oxa-4-pentene sulfonic acid) copolymer aqueous dispersion with a solid content of 25%. The trade name is D72-25BS. 200 g of fluorinated emulsion A and 24 g of fluorinated emulsion B were mixed and mechanically stirred for 15 min to obtain a fluorinated polymer aqueous emulsion, and the solid mass ratio of the two resins was 20:1.
[0045] Add 25.2 g of MnO with a mass ratio of 2:1 to the above solution. 2 and MgO mixed powder, the particle diameter is greater than 300 mesh, accounting for 20% of the solid mass of the fluorine-containing polymer aqueous emulsion. Then add 3.15g 300 mesh carbon nanotube powder, accounting for 2.5% of the solid mass of the fluorine-containing polymer aqueous emulsion. Transfer to an ice water bath and obtain a catalyst suspension by ultrasonic emulsification.
[0046] The film was formed by using high boron glass as the substrate, coating speed of 75 mm / s, coating thickness of 0.5 mm, bottom plate temperature of 90°C, and continuous drying time of 5 min. The sintering conditions were heating rate of 10°C / min, maximum temperature of 280°C, and heat preservation for 20 min. The cooled film was cut into 3-5 mm thin slices, washed with pure water, and dried to obtain the ozone fluidized bed catalyst.
[0047] The fluidization condition when the catalyst volume expands by 50% is the aeration intensity of 2.07 L / (m 2хs), backwash intensity is 0.302L / (m 2 хs). The attrition weight loss percentage of the catalyst is L 1h <4.6%. The catalyst dosage for the test reaction was about 600mL, the ozone / oxygen mixed gas flow rate was adjusted to 1.5L / min, the ozone concentration was stabilized at 60-65mg / L, the reflux pump flow rate was 7L / h, and the virtual wastewater with COD=800mg / L was treated under the above conditions. The average COD removal rate after 1h of reaction was about 75%.
[0048] Embodiment 3:
[0049] Fluorine-containing emulsion A is a polytetrafluoroethylene resin (PTFE) emulsion with a solid content of 60%, and fluorine-containing emulsion B is a tetrafluoroethylene-perfluoro (3-oxa-4-pentene sulfonic acid) copolymer aqueous dispersion with a solid content of 25%. The trade name is D72-25BS. 200 g of fluorinated emulsion A and 12 g of fluorinated emulsion B were mixed and mechanically stirred for 15 min to obtain a fluorinated polymer aqueous emulsion, and the solid mass ratio of the two resins was 40:1.
[0050] Add 18.5 g of CuO, MgO and CeO in a mass ratio of 2:1:1 to the above solution. 2 The mixed powder has a particle diameter greater than 300 mesh, accounting for 15% of the solid mass of the fluoropolymer aqueous emulsion. Then 2.46g of 800 mesh activated carbon powder is added, accounting for 2% of the solid mass of the fluoropolymer aqueous emulsion. The mixture is transferred to an ice-water bath and ultrasonically emulsified to obtain a catalyst suspension.
[0051] The film was formed by using high boron glass as the substrate, coating speed of 50 mm / s, coating thickness of 1.0 mm, bottom plate temperature of 105°C, and continuous drying time of 5 min. The sintering conditions were heating rate of 10°C / min, maximum temperature of 280°C, and heat preservation for 30 min. The cooled film was cut into 3-5 mm thin slices, washed with pure water, and dried to obtain the ozone fluidized bed catalyst.
[0052] The fluidization condition when the catalyst volume expands by 50% is the aeration intensity of 2.59 L / (m 2 хs), backwash intensity is 0.604L / (m 2 хs). The attrition weight loss percentage of the catalyst is L 1h <2.5%. The catalyst dosage for the test reaction was about 600mL, the ozone / oxygen mixed gas flow rate was adjusted to 1.5L / min, the ozone concentration was stabilized at 60-65mg / L, the reflux pump flow rate was 10L / h, and the virtual wastewater with COD=800mg / L was treated under the above conditions. The average COD removal rate after 1h of reaction was about 88%.
[0053] Comparative Example 1:
[0054] The carrier of the ozone fluidized bed catalyst is 30-mesh gamma alumina particles, and the catalytic active components are loaded by the impregnation method known in the industry, specifically an aqueous solution of Fe and Mn sulfates in a mass ratio of 2:1, and a water-dispersed mixed solution obtained by urea reduction. The total amount of active components loaded is 15% of the carrier mass. The impregnated catalyst is first dried and then calcined at 550°C for 4 hours in an air atmosphere to finally obtain a finished comparative fluidized bed catalyst.
[0055] The fluidization condition when the catalyst volume expands by 50% is the aeration intensity of 4.14 L / (m 2 хs), backwash intensity is 2.41L / (m 2 хs). The abrasion-resistant weight loss percentage of the catalyst is L1h<6.5%. The catalyst dosage for the test reaction is about 1L volume, the ozone / oxygen mixed gas flow rate is adjusted to 1.5L / min, the ozone concentration is stabilized at 60-65mg / L, the reflux pump flow rate is 14L / h, and the virtual wastewater with COD=800mg / L is treated under the above conditions. The average COD removal rate after 1h of reaction is about 78%.
[0056] Comparative Example 2:
[0057] The carrier of the ozone fixed bed catalyst is a φ3-5mm gamma alumina ball. The catalytic active components are loaded by the impregnation method known in the industry. Specifically, the Fe and Mn sulfate aqueous solution with a mass ratio of 2:1 is used, and the water-dispersed mixed solution is obtained by urea reduction. The total amount of active components loaded is 15% of the carrier mass. The impregnated catalyst is first dried, dried and calcined at 550°C in air atmosphere to finally obtain the fixed bed catalyst product. The fixed bed catalyst with a loading volume of 60% is used for ozone catalytic oxidation, and the COD removal rate is 65%.
[0058] The data analysis of the embodiments and comparative examples is shown in the following table.
[0059]
[0060] a COD=800mg / L,O 3 :COD=2:1, ozone mixed gas flow rate 1.5L / min
[0061] From the data analysis of the embodiment and the comparative example, it can be seen that the ozone fluidized bed catalyst in this embodiment has a low dosage and has lower fluidization dynamic conditions.
Claims
1. A method for preparing an ozone fluidized bed catalyst, characterized in that: The following steps are involved: Step 1, preparing a fluorine-containing polymer aqueous emulsion; Step 2: adding a certain mass of carbon-based material powder and catalyst powder into the fluorine-containing polymer aqueous emulsion and dispersing them into a catalyst suspension; Step 3, applying the catalyst suspension to the substrate by a wet coating method, and preparing a catalyst film by solvent drying, sintering, cooling, peeling and washing; Step 4: Cut the catalyst film into a certain size to finally obtain a fluidized bed catalyst.
2. The method for preparing an ozone fluidized bed catalyst according to claim 1, characterized in that: The fluorine-containing polymer aqueous emulsion in step 1 is composed of fluorine-containing emulsion A and fluorine-containing dispersion B, and the effective solid mass ratio of fluorine-containing emulsion A to fluorine-containing dispersion B is 40-80:1; the fluorine-containing emulsion A is a polytetrafluoroethylene resin aqueous emulsion, and the fluorine-containing dispersion B is a perfluorosulfonic acid resin dispersion; the solid content of the fluorine emulsion A is 45-70%, and the average diameter of the polytetrafluoroethylene resin is 0.2-0.5 μm; the solid content of the fluorine-containing dispersion B is 10-25%, and the average diameter of the fluorinated resin is 0.05-0.1 μm.
3. The method for preparing an ozone fluidized bed catalyst according to claim 2, characterized in that: The fluorine-containing dispersion B is a perfluorosulfonic acid-based resin dispersion prepared from an unsaturated perfluoroolefin monomer and a perfluorovinyl ether monomer containing at least one -SO2F functional group.
4. The method for preparing an ozone fluidized bed catalyst according to claim 3, characterized in that: The unsaturated perfluoroolefin monomer is one of the C2-C6 perfluoroolefins; the general chemical formula of the perfluorovinyl ether monomer is F2C=CF-O-[CF2]n-SO2F, wherein n=1-4.
5. The method for preparing an ozone fluidized bed catalyst according to claim 1, characterized in that: The carbon-based material powder in step 2 is powdered activated carbon or carbon nanotubes or graphene, the carbon-based material powder accounts for 0.5%-4% of the solid content of the fluorine-containing polymer aqueous emulsion, and the particle size of the carbon-based material powder is 800 meshes.
6. The method for preparing an ozone fluidized bed catalyst according to claim 1, characterized in that: The catalyst powder in step 2 is 1-3 of the oxide powders of Fe, Mn, Cu, Ni, Ce, Mg, Sn, Bi, Ag and Au, the catalyst powder accounts for 5%-30% of the solid content of the fluoropolymer aqueous emulsion, and the particle size of the catalyst powder is greater than or equal to 300 meshes.
7. The method for preparing an ozone fluidized bed catalyst according to claim 1, characterized in that: In step 3, the wet coating method uses high boron glass or stainless steel plate material as the substrate, the coating speed is 5-250 mm / s, the coating thickness range is 0.1-10 mm, and the bottom plate heating range is RT-180°C.
8. The method for preparing an ozone fluidized bed catalyst according to claim 1, characterized in that: In step three, the sintering temperature is 200-280°C, the heating rate is 10°C / min, and the maximum temperature sintering time does not exceed 30min; the cooling condition is to stop heating until the temperature drops below 150°C; the rinsing condition is to rinse with pure water until the rinsing liquid no longer bubbles and is neutral.
9. The method for preparing an ozone fluidized bed catalyst according to claim 1, characterized in that: In step 4, the catalyst film is cut into square sheets with a side length of 3-5 mm.
10. An ozone fluidized bed catalyst characterized by: Prepared by any one of claims 1-9.
Citation Information
Patent Citations
Catalytic Ozone Oxidation Fluidized Bed Reactor for Efficient Removal of CODcr in Wastewater
CN104529001B
Device and system for fluidized bed type catalytic ozonation three-phase separation reaction
CN110818064A
Internal circulation catalytic ozonation reactor and method for treating wastewater by internal circulation catalytic ozonation reactor
CN114684972A
Ozone fluidized bed catalyst as well as preparation method and application thereof
CN115591554A
Catalytic ozonation fluidized bed sewage treatment device
CN213506156U
Cited By
Efficient flocculation, ozone catalysis and membrane distillation combined process for purifying high-salinity wastewater
CN119977222A